2020
DOI: 10.5937/afmnai2002139m
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and crystal chemical characteristics of gallbladder biomineralization

Abstract: Pathological biomineralization can be found in some gallbladder (GB) diseases such as chronic calculous cholecystitis (CCCh), gallbladder cancer (GBC) and porcelain gallbladder (PGB).The aim of the work was to analyze the morphology of pathological biomineralization in GB tissue in CCCh, GBC and PGB.Five cases of PGB, 10 samples of CCCh and 5 cases of GBC with biomineralization were selected for this study. All samples were examined by histology, histochemistry and scanning electron microscopy with X-ray diffr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…X-ray diffraction revealed that all pathological minerals were represented by calcium apatite with different levels of crystallinity (Figure 5). Similar results were previously published for biominerals of the gallbladder, prostate and thyroid gland [16,17].…”
Section: Temsupporting
confidence: 91%
See 1 more Smart Citation
“…X-ray diffraction revealed that all pathological minerals were represented by calcium apatite with different levels of crystallinity (Figure 5). Similar results were previously published for biominerals of the gallbladder, prostate and thyroid gland [16,17].…”
Section: Temsupporting
confidence: 91%
“…The mineral component of macroscopic calcifications was separated from soft tissues by heat treatment at 200 • C for 1 h. This contributed to the destruction of the organic compounds of the calcification and the removal of water residues while maintaining the structure of the crystallite. Pathological biomineral formations with a diameter of less than 0.05 cm were detected by histology and scanning electron microscopy from histological sections of tumor tissue [16].…”
Section: Detection Of Pathological Biomineralsmentioning
confidence: 99%